IMPLEMENTASI PENGGUNAAN MEDIA PEMBELAJARAN ONLINE PADA PEMBELAJARAN DARING MATA PELAJARAN MATEMATIKA - Wahyuning Putri Bima; Lintang Yanuarita; Adi Nurcahyo (Buletin Literasi Budaya Sekolah, 2021)
This study aims to obtain data and information related to the implementation of the use of online learning media in online learning in mathematics. This study uses qualitative research methods through descriptive explanations to find out an overview of the use of online learning media in online mathematics learning. Participants in this study were students of SMP Negeri 1 Juwiring class VIII E, F, G, H and the math teacher in that class. Data collection was carried out by interview, direct observation, learning value, documentation and distributing questionnaires to students. The results of this study are teachers using whatsapp group and google classroom in online learning, unstable internet network, lack of student understanding of the material, and the number of assignments given. Learning online is less effective because the teacher only provides material and assignments. Teachers can increase learning online outcomes with present material through LMS, provide guidance and communication to students in need, and improve teacher skills in learning.